Substances, relationships and the omnipresence of the body: an overview of Ashéninka ethnomedicine (Western Amazonia) - Lenaerts Marc (BMC, 2006)
Abstract Indigenous Amazonian ethnomedicine usually relies on numerous forms of healing, exercised by both specialists and non-specialists. Such is the case among the "Asheninka del Ucayali" (Arawak from the Peru-Brazil border). This paper attempts to elicit the underlying consistencies of their manifold, often contradictory practices and statements. It draws on ethnographic data gathered between 1997 and 2000, and is essentially based on my own interviews and participant observation. Concerning some specific points these data are also compared with ethnobotanical findings, to highlight significant peculiarities of the Asheninka approach. The first question is about the nature of a "good medicine". When the Asheninka borrow botanical knowledge from another ethnic group and comment the fact, the contrast between indigenous self-assessments and objective ethnobotanical measurements points out a crucial difference: While the Western approach focuses essentially on chemical effectiveness of the plants themselves, Asheninka people pay much more attention to relational aspects. The relational dimension also involves the plants themselves, as a sort of person. The point has implications in Asheninka shamanism and herbalism. A shaman does not necessarily need to be a good botanist. His main concern is managing a network of personal relationships involving all kinds of living beings. This network is supposed to be the mainspring of illness - a belief shared by both shamans and ordinary people. However, most ordinary people have detailed herbal knowledge. In fact, this everyday herbalism amounts to an alternative explanatory model. Such a coexistence of two contrasting explanatory systems is frequent in Amazonia. Among the Asheninka, nevertheless, the underlying hierarchy is clear: the herbal, apparently more materialistic, approach is embedded in the shamanic, plainly relational, model.